THE GENDERED CONSTRUCTION OF LEADERSHIP AND FOLLOWERSHIP IN ARMENIA’S EDUCATIONAL SYSTEM - Gevorgyan, Hasmik (Journal of Sociology: Bulletin of Yerevan University, 2025)
This article analyzes the gendered construction of leadership and followership within Armenia’s educational system, drawing on theoretical frameworks from gender studies and qualitative fieldwork conducted in public schools. Despite the heavy feminization of the teaching profession, authority and leadership in Armenian society remain culturally coded as masculine, producing a structural paradox in which women educators hold formal instructional authority yet encounter symbolic devaluation. Empirical findings from interviews and classroom observations show that these gendered expectations shape how authority is interpreted and enacted, particularly in male students’ varied acceptance or resistance to women as legitimate knowledge holders. The study demonstrates that gendered cultural norms continue to structure leader–follower relations in educational contexts and argues for a more critical engagement with how institutional practices reproduce or challenge patriarchal assumptions. The study contributes to scholarship on gender and educational leadership by demonstrating how cultural schemas and institutional norms continue to influence authority relations within Armenian schools
Keywords: archetypes; archetypes, collective unconsciousness, critical frame, education, followership, gender, leadership, stereotypes; critical frame; education; followership; gender; leadership; stereotypes